DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

On the Internet by Means of Popular Music: The Cases of Grimes and Childish Gambino - Ohlendorf, Kristopher R. K. (Université Western Ontario, 2016)
What is the internet? It began as a military research experiment, but the internet has since become a sweeping cultural phenomenon. One of the most prevalent areas of the internet’s cultural dominance is in popular music, and this thesis addresses how the internet is being understood and discussed by popular music artists. I study the works of Grimes and Childish Gambino, two popular music artists who grew up alongside the internet’s rise to cultural dominance and explicitly address this experience as an integral component of their lives and works. I look specifically at discourse surrounding Grimes’ “post-internet” music and Childish Gambino’s expansive conceptual work Because the Internet (2013). This research concludes by addressing how popular music artists like Grimes and Childish Gambino are helping produce the ways in which we understand and discuss the cultural phenomenon of the internet, and how they provide a foundation for future artists and research to build upon.